Cooperative adsorption-degradation of benzo[a]pyrene by extracellular enzymes of white rot fungi immobilized on macroporous adsorption resin. (March 2023) - Du, Xuran; Wang, Litao; Li, Ying; Wu, Jing; Chen, Guanyu; Liang, Hong; Gao, Dawen
Abstract: Adsorption technology has been widely used in water purification, but its removal mechanism mainly depends on the enrichment and transformation of pollutants, and it cannot be completely degraded. Based on the adsorption properties of macroporous adsorbent resins and the biodegradation of extracellular enzymes of white rot fungi, a synergic study on the adsorption and degradation of benzo[a]pyrene in water was conducted in this paper. The results of the eight-resin screening exhibited that the resin AB-8 exhibited the best immobilization effect of enzymes and removal rate of benzo[a]pyrene. The removal of benzo[a]pyrene by immobilized enzymes and adsorption resin followed pseudo-secondary kinetics, while the degradation of benzo[a]pyrene by free enzymes followed first-order kinetics. Immobilized enzymes can achieve the adsorption-degradation of benzo[a]pyrene, its removal rate reached 92.78% after 6h, which is higher than the degradation rate of free enzymes and faster than the resin adsorption. After that, molecular docking indicated that van der Waals forces and Pi-Alkyl attributed to the binding of laccase and benzo[a]pyrene. Physical adsorption synergistic biodegradation technology is of great practical significance and theoretical value for the sustainable treatment of polluted water. Highlights: Immobilized enzymes with AB-8 were proposed to synergistically absorb and degrade benzo[a]pyrene. Cooperative adsorption-degradation follows pseudo-secondary kinetics. Laccase binds to benzo[a]pyrene mainly through van der Waals forces and Pi-Alkyl.